Immigration and Occupations in Europe - Francesco D'Amuri; Giovanni Peri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
In this paper we analyze the effect of immigrants on natives' job specialization in Western Europe. We test whether the inflow of immigrants changes employment rates or the chosen occupation of natives with similar education and age. We find no evidence of the first and strong evidence of the second: immigrants take more manual-routine type of occupations and push natives towards more abstract-complex jobs, for a given set of observable skills. We also find some evidence that this occupation reallocation is larger in countries with more flexible labor laws. As abstract-complex tasks pay a premium over manual-routine ones, we can evaluate the positive effect of such reallocation on the wages of native workers. Accounting for the total change in Complex/Non Complex task supply from natives and immigrants we find that immigration does not change much the relative compensation of the two types of tasks but it promotes the specialization of natives into the first type.
Keywords: J24; J31; J61; 330; immigration; task specialization; European labor markets